The factor-spline-GARCH model for high and low frequency correlations - Jose Gonzalo Rangel; Robert F. Engle (Banco de México, 2009)
We propose a new approach to model high and low frequency components of equity correlations. Our framework combines a factor asset pricing structure with other specifications capturing dynamic properties of volatilities and covariances between a single common factor and idiosyncratic returns. High frequency correlations mean revert to slowly varying functions that characterize long-term correlation patterns. We associate such term behavior with low frequency economic variables, including determinants of market and idiosyncratic volatilities. Flexibility in the time varying level of mean reversion improves the empirical fit of equity correlations in the US and correlation forecasts at long horizons.
Keywords: C22; C32; C51; C53; G11; G12; G32; 330; Factor models; Low frequency volatilities and correlations; Dynamic conditional correlation; Spline-GARCH; Idiosyncratic volatility; Long-term correlation forecasts